2022
DOI: 10.1371/journal.pone.0270766
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an asynchronous telerehabilitation program in post-COVID-19 patients: A protocol for a pilot randomized controlled trial

Abstract: Background About 40% of patients who have had COVID-19 still have symptoms three months later whereas a 10% may experience physical and/or psychological consequences two years later. Therefore, it is necessary to perform preventive interventions when patients are discharged from the hospital to decrease the aforementioned sequelae. The purpose of this pilot-controlled trial will be to determine the efficacy of a rehabilitation program on functional status and psychosocial factors for post-COVID-19 patients whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 100 publications
0
1
0
Order By: Relevance
“…Through educational movies, the therapeutic education recommendations were explained to the patients, giving them health and emotional advice on how to improve their QoL after COVID-19. They reported that telerehabilitation led to a clinical improvement in QoL, particularly in the physical component [ 25 ]. These interventions can provide individuals with access to rehabilitation programs in the comfort of their own homes.…”
Section: Discussionmentioning
confidence: 99%
“…Through educational movies, the therapeutic education recommendations were explained to the patients, giving them health and emotional advice on how to improve their QoL after COVID-19. They reported that telerehabilitation led to a clinical improvement in QoL, particularly in the physical component [ 25 ]. These interventions can provide individuals with access to rehabilitation programs in the comfort of their own homes.…”
Section: Discussionmentioning
confidence: 99%
“…To continue with pre-rehabilitation interventions in cancer patients during the pandemic, it was necessary to look for other intervention alternatives, which has required a change in the daily functioning of health systems, both in Chile and in the rest of the world. This is how recent studies report that show the implementation of telerehabilitation in different contexts, including oncosurgical patients [8,9] It has been shown to be safe, feasible, well received by patients and offers good results for cancer survivors [8][9][10][11] In our country, there is little evidence in relation to telerehabilitation in oncosurgical patients [4] and even more, from the perspective of patients the information is non-existent. The main objective of this study is to describe the implementation of a telerehabilitation program during the COVID-19 pandemic for patients who are candidates for elective cancer surgery in a low-income Chilean public hospital.…”
Section: Introductionmentioning
confidence: 99%